AWARENESS, PERCEPTION, ATTITUDE AND EXPECTATIONS OF UNIVERSITY STUDENTS TOWARDS HALAL FOOD - Özkan, Bekir (Kafkas Üniversitesi, 2022)
The study aims to determine the awareness, perception, attitude and expectations of consumers about halal food. In the study, the survey method is used as a data collecting technique. As a sample collecting technique, snowball sampling, a nonprobability sample collecting procedure, is used. The survey is sent to university students via social media such as Facebook and Instagram, and have been asked to fill it out and share it with their friends. According to results, university students define halal food as; “food that does not contain any substance that is haram”, “does not contain pork and its derivatives”, “animal slaughtered according to Islamic conditions”, “not haram”, “great effort, halal income” etc. And, the information source consumers care most about and trust the most regarding halal and healthy food are food experts. The second most trusted source is religiously sensitive people and the third most trusted source is theologists.

Araştırmanın ana amacı, tüketicilerin helal gıda konusundaki farkındalıklarının, algılamalarının, tutumlarının ve beklentilerinin ortaya çıkarılmasıdır. Araştırmada veri toplama yöntemlerinden anket kullanılmıştır. Örneklem toplama metodu olarak tesadüfi olmayan örnekleme yöntemlerinden kartopu örnekleme yöntemi kullanılmıştır. Söz konusu anket üniversite öğrencilerine facebook ve instagram gibi sosyal medya mecraları üzerinden gönderilmiş, anketi cevaplamaları ve arkadaşlarına da dağıtmaları istenmiştir. Elde edilen sonuçlara göre, üniversite öğrencileri helal gıdayı; “içeriğinde haram hiçbir madde olmayan”, “domuz ve türevlerini içermeyen”, “İslami şartlara göre kesilen hayvan”, “haram olmayan”, “alın teri, helal kazanç” vb. olarak tanımlamaktadırlar. Helal gıda konusunda tüketicilerin en çok önem verdiği ve en çok güvendiği bilgi kaynağı ise, “gıda uzmanları” dır. İkinci olarak en çok güvenilen kaynak ise, “Dinî hassasiyeti olan kişiler” ve üçüncü olarak en çok güvenilen kaynak ise, “ilahiyatçılar” dır.
AWARENESS, PERCEPTION, ATTITUDE AND EXPECTATIONS OF UNIVERSITY STUDENTS TOWARDS HALAL FOOD